2011
DOI: 10.1111/j.1471-4159.2011.07320.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking extranigral degeneration in animal models of Parkinson’s disease: quest for effective therapeutic strategies

Abstract: Sporadic Parkinson’s disease (PD) is now interpreted as a complex nervous system disorder in which the projection neurons are predominantly damaged. Such an interpretation is based on mapping of Lewy body (LB) and Lewy neurite (LN) pathology. Symptoms of the human disease are much widespread, which span from preclinical nonmotor symptoms and clinical motor symptoms to cognitive discrepancies often seen in advanced stages. Existing symptomatic treatments further complicate with overt drug-irresponsive symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 133 publications
0
6
0
2
Order By: Relevance
“…PD is also associated with the presence of ubiquitin- and α-synuclein-positive cytoplasmic inclusions known as Lewy bodies within surviving dopaminergic neurons [6]. In addition to the nigrostriatal dopaminergic defects, emerging clinical evidence suggests that extranigral degeneration and non-motor symptoms are key features of early stages of PD pathogenesis [7-10]. …”
Section: Introductionmentioning
confidence: 99%
“…PD is also associated with the presence of ubiquitin- and α-synuclein-positive cytoplasmic inclusions known as Lewy bodies within surviving dopaminergic neurons [6]. In addition to the nigrostriatal dopaminergic defects, emerging clinical evidence suggests that extranigral degeneration and non-motor symptoms are key features of early stages of PD pathogenesis [7-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Conjoint lines of evidence from clinical reports and experimental studies have suggested degeneration of spinal cord in PD as outlined in recent reviews (Knaryan et al . ; Vivacqua et al . ).…”
mentioning
confidence: 99%
“…Similar alterations occur in rodent motor neurons in genetic and toxin-induced PD models (described in detail below). These were associated with signs of muscle dystrophy (Knaryan et al, 2011; Lee et al, 2002; Samantaray et al, 2008; Vivacqua et al, 2009), but the pathology of somatosensory neurons of the dorsal root ganglia or trigeminal ganglia has not been studied in rodents.…”
Section: Nociceptive Neurons In Pdmentioning
confidence: 99%